حركة التغير في ليبيا - الحمداني، كفاح عباس رمضان (جامعة الموصل - مركز الدراسات الإقليمية, 2014)
سرعان ما امتدت رياح التغيير إلى ليبيا، بعد أن اجتاحت حركة التغيير في تونس ومصر واستطاعت هاتان الثورتان أن تحققان مطالب الشعب التونسي والمصري في إزاحة نظام الحاكم فيهما، وقيام حكومة وطنية جديدة تسعى إلى تحقيق مطلب الشعب. واتسمت حركة التغيير في ليبيا بأنها الأعنف والأقوى قياسا بحركات التغيير العربية الأخرى التي سبقتها، والتي أدت إلى التدخل الدولي لإزاحة النظام الحاكم في ليبيا، وبفضل التدخل الدولي وإصرار الشعب الليبي على أحداث التغيير استطاع الشعب الليبي أن يحقق مطالبه في إزاحة النظام الحاكم في ليبيا. إن الحكم على الثورة الليبية وتقييم مسارها خلال السنوات القادمة، سيكون من خلال تحقيق أهدافها بالدرجة الأولى، لكن الأهم من ذلك هو النجاح الذي ما يزال ينتظره الشعب الليبي الذي أنتج هذه الثورة المتمثل بتحقيق مطالبه السياسية والاقتصادية والاجتماعية التي ضحى من أجلها. Quickly spread the winds of change to Libya, having swept the movement of change in Tunisia and Egypt and these revolutions has been able to achieve the demands of the Tunisian and Egyptian people to dislodge the ruling system in them, and do a new national government seeks to achieve the demands of the people. And characterized by the Movement Change in Libya as violent and powerful analogy movements change other Arab predecessors, and that led to international intervention to topple the regime in Libya, and thanks to international intervention and insistence of the Libyan people to make a difference could the Libyan people to achieve their demands to dislodge the regime in Libya. The judgment of the Libyan revolution and evaluate its course in the coming years, it will be through the achievement of its objectives primarily, but more importantly it is a success, which is still waiting for the Libyan people who produced this revolution, is to achieve political and economic demands and social which they sacrificed.
Keywords: الثورة الليبية; الثورات العربية; ليبيا